Toxic Ag+ detection based on Au@Ag core shell nanostructure formation using Tannic acid assisted synthesis of Pullulan stabilized gold nanoparticles - Titilope John Jayeoye; Chamaiporn Supachettapun; Nongnuj Muangsin (Scientific Reports, 2023)
Abstract Herein, a sensitive colorimetric detection strategy is proposed for Ag+ detection based on the use of environmentally friendly synthesis of gold nanoparticles (AuNPs), at room temperature, using (tannic acid, TA), as the reductant and pullulan (PUL) as stabilizing agent. The colloidal solution (TA/PUL-AuNPs), at the optimal synthesis conditions, showed maximum absorbance at 529 nm with a berry red color. TEM and FESEM validated that the particles are spherical and monodispersed, while other characterization results elucidated the role of pullulan in the nano-synthesis. Ag+ addition to the probe (TA/PUL-AuNPs), pH 11, resulted in naked-eye color changes, owing to Au@Ag core shell nanostructure formation. Further, the added Ag+ is reduced to AgNPs, on the surface of the TA/PUL-AuNPs probe. A hypsochromic shift in the absorption maximum, from 529 to 409 nm was observed, while (AAg+-Abl)@409 nm exhibited linearity with Ag+ concentrations, from 0.100 to 150 µM. The estimated limit of detection was 30.8 nM, which is far lower than the acceptable limit of 0.930 µM from the regulatory agency. The TA/PUL-AuNPs probe was further tested for Ag+ detection in lake water samples, and it displayed satisfactory detection performances for real sample applications.